Nanophotonic perfect absorber with ultra-broadband terahertz-to-infrared response via hybrid-material design for advanced optical sensing - Musa N. Hamza; Mohammad Tariqul Islam; Sunil Lavadiya; Iftikhar ud Din; Bruno Sanches; Slawomir Koziel; Syeda Iffat Naqvi; Ali Farmani; Abinash Panda; Md. Shabiul Islam (PLoS ONE, 2026)
The terahertz (THz) frequency range has gained significant attention in recent years, particularly for applications in biological diagnostics, remote sensing, security systems, and wireless communications. One key advantage of THz radiation is that it is safer than X-rays while offering higher data rates and enhanced channel capacity. THz systems encapsulate several components, including absorbers, which play a crucial role in stealth technologies, detection, and high-resolution imaging. Many absorber designs in the literature are based on metamaterials; however, these structures tend to be physically large and thick, limiting their integration into devices. This research introduces an innovative, compact THz-range sensor designed for biomedical applications. The sensor features a geometrically simple structure, utilizing silver (Ag) and nickel (Ni) resonators embedded on a silicon dioxide (SiO2) dielectric substrate. The device measures only 100 × 100 nm², with the Ag, SiO2, and Ni layers totaling just 26 nm thickness. This material and geometric arrangement achieve near-perfect absorptivity (>99.9%) across the operating range up to 30 THz. Extensive numerical studies demonstrate the sensor’s excellent performance, analyzed through surface current, electric, and magnetic field distributions. Compared to state-of-the-art benchmarks, comprehensive comparative studies reveal the sensor’s superior performance in terms of operating range, compact size, absorption efficiency, and angular stability. Its exceptional sensitivity and ability to detect subtle changes in tissue refractive index make it ideal for early-stage cancer detection and other biomedical applications. Additionally, it is well-suited for real-time detection of environmental pollutants and security screening.